Proteomics analysis of serum protein patterns in duck during aflatoxin B1 exposure - Natthasit Tansakul; Jatuporn Rattanasrisomporn; Sittiruk Roytrakul (Veterinary World, 2019)
Background and Aim: Unlike the already well-documented human serum proteome, there are still limitations regarding analyzing and interpreting the various physiological changes and disease states of the serum proteomes found in duck. Serum proteome in duck under the condition of mycotoxin contamination in feed has not yet been examined. This study aimed to introduce the characterization of the circulating proteomes in duck serum during exposure to aflatoxin B1 (AFB1).